(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
This article examines how temporal concepts intersect with artistic expression in Enlightenment dramaturgy, comparing the theatrical traditions of England and Uzbekistan. Through a comparative analysis of pivotal plays, the research investigates how playwrights from these distinct cultural milieus depicted temporal themes and employed artistic techniques to convey philosophical and societal ideals during the 17th and 18th centuries. By juxtaposing English and Uzbek Enlightenment drama, this study seeks to uncover the cultural and philosophical underpinnings that influenced their respective artistic representations of time.